A Systematic Literatur Review: Exploring the Rich Heritage of Indonesian Cuisine through the Versatile Peanut Ingredient - Nur Agustin Mardiana; Hyldegardis Naisali (Universitas Islam Raden Rahmat, Malang, 2023)
Peanuts are widely used in Indonesian cuisine as a source of protein and vital fats, and they provide an exceptional nutritional profile that meets the needs of the country's diet. Peanuts, or